1993
DOI: 10.1128/mcb.13.1.358
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a thyroid tumor-specific transforming sequence formed by the fusion of ret tyrosine kinase and the regulatory subunit RI alpha of cyclic AMP-dependent protein kinase A.

Abstract: The ret oncogene frequently has been found activated in papillary thyroid carcinomas. A previous characterization of ret activation revealed recombination of its tyrosine kinase domain and sequences derived from an uncharacterized locus (DlOS170). The mechanism leading to this recombination was identified as a paracentric inversion of the long arm of chromosome 10, inv(10)(qll.2q21), with the breakpoints occurring where ret and DlOS170 were mapped. To further characterize the activation of ret in papillary thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
129
0
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(134 citation statements)
references
References 15 publications
3
129
0
2
Order By: Relevance
“…In fact, we had previously demonstrated that heterodimerization between the two isoforms can occur (Bongarzone et al, 1993) and, as a consequence, here we have observed that pY620 inhibits the binding of Grb2 with both isoforms.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In fact, we had previously demonstrated that heterodimerization between the two isoforms can occur (Bongarzone et al, 1993) and, as a consequence, here we have observed that pY620 inhibits the binding of Grb2 with both isoforms.…”
Section: Discussionsupporting
confidence: 65%
“…The experiments were performed with constitutively activated oncogenic Ret versions, encoded by RET/PTC2 (Bongarzone et al, 1993), a thyroid carcinoma-speci®c oncogene generated by a somatic rearrangement of RET and by RET-C634R , a RET point mutant associated to the inherited cancer syndrome MEN2A. The two oncogenic proteins represent cytosolic and membranebound forms of Ret kinase, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the second question, we are unable to verify it because we do not have enough biological material to study by XL-PCR the genomic sequences where the break-points are generally located in the different RET/PTC rearrangements known until present (Grieco et al, 1990;Bongarzone et al, 1993;Santoro et al, 1994;Fugazzola et al, 1996;Bounacer et al, 1997;Suárez, 1998b). Finally, concerning the third question, there was no evidence in the clinical history of our patients of a possible low-dose irradiation and/or a chemical agent aggression.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, contrasting with the high and very similar frequency (about 60%) of activation by rearrangement observed in the therapeutic or accidental radiation-associated tumours (Bounacer et al, 1997), the frequency of ret activation by this mechanism in 'spontaneous' thyroid tumours varies widely between different studies: from 2.5% to 34% (Bongarzone et al, 1989(Bongarzone et al, , 1993Grieco et al, 1990;Santoro et al, 1994;Delvincourt et al, 1996;Bounacer et al, 1997). It has been postulated that this variation observed in 'spontaneous' tumours, could be the result of the different geographical origins of populations studied, the age at tumour occurrence, or the sensitivity of the experimental methods used to detect the rearrangement.…”
mentioning
confidence: 85%
“…In thyrocytes, another alteration of ret, chimerical proteins named ret/PTC generated by chromosomal translocation, may cause papillary thyroid carcinoma. The 3' tyrosine kinase domain of ret is fused to the 5' part of the H4 (PTC1), Rla (PTC2) or elel (PTC3) gene, resulting in constitutional expression of ret and phosphorylation of ret and other target proteins (Grieco et al, 1990;Bongarzone et al, 1993;Santoro et al, 1994). This event was specific for papillary thyroid carcinoma (Santoro et al, 1993), but the reported frequencies varied widely from 2.5% to 30% of these tumours Zou et al, 1994).…”
mentioning
confidence: 99%